Causal role of immunophenotypes in HIV-1 acquisition: insights from Mendelian randomization analysis - Nan Li; Chuan He (Scientific Reports)
Abstract The acquisition of human immunodeficiency virus (HIV) is influenced by environmental and genetic factors, such as viral inoculum dose, host behavior, and immune responses. Despite advances in understanding HIV pathogenesis, no effective vaccine exists, underscoring the urgent need to deepen our comprehension of host immune mechanisms to enhance preventive strategies. Genetic predisposition and certain immunity characteristics of the host might play essential roles in the risk of HIV-1 acquisition. Mendelian randomization (MR) and colocalization analysis are utilized to investigate the causal relationships between immune responses and HIV-1 risk, aiming to identify targets for potential eradication strategies. We employed a two-sample MR approach to explore the causal links between 731 immunophenotypes and HIV-1 acquisition, using genetic variants from publicly available GWAS summary statistics as instrumental variables. Sources included GWAS data for immune traits and a meta-analysis from European cohorts for HIV-1 acquisition. We validated our findings using Summary-data-based MR analysis, integrating eQTL and mQTL data from the GTEx project. Bayesian colocalization analysis was conducted to identify shared causal variants. Functional and pathway enrichment analysis employing Metascape and Enrichr websets were performed to elucidate potential biological pathways linking immunephenotypes to HIV-1 risk. Our MR analysis identified significant causal associations between 26 specific immunophenotypes and HIV-1 acquisition, indicating a causal association with HIV risk. Colocalization analysis showed that none demonstrated genome-wide evidence of genetic colocalization (regional PP.H4.abf > 0.70). SMR and HEIDI analysis confirmed pleiotropic associations, particularly noting CCR2 on granulocytes as significant. Functional enrichment analysis of 39 SMR-identified genes revealed critical pathways linking immunophenotypes to HIV-1 susceptibility. The “NABA MATRISOME ASSOCIATED” canonical pathway emerged as the most significant pathway using Metascape. Protein–protein interaction networks demonstrated 5 functionally cohesive clusters. Multi-database analyses using Enrichr Analysis revealed functionally similar pathway enrichment: Cell cycle regulation (“G2 Phase”, Reactome; “G1/S Control”, WikiPathways), shedding light on crucial immune regulation mechanisms potentially instrumental in HIV-1 acquisition.